Incomplete miscarriage during the first trimester: a comparison of indoor versus outdoor procedure - FaizaIqbal,SadiaAzmat,RabiaJamshaid,ZunairaArshad,AnumSaqib, FaizaIqbal,SadiaAzmat,RabiaJamshaid,ZunairaArshad,AnumSaqib (Journal of Rawalpindi Medical College, 2020)
Introduction: Miscarriage is defined as the natural death of a fetus inside the uterus. To remove complete conception material after a miscarriage, vacuum aspiration or dilatation & curettage are methods to remove uterine contents. Controversies exist regarding both procedures. So we conducted this study to confirm the more successful method. Objective: To compare the effectiveness of manual vacuum aspiration versus traditional evacuation and curettage (E & C) among females presenting with incomplete miscarriage during the first trimester of pregnancy Materials and Methods: This randomized controlled trial was done at the Department of Obstetrics & Gynecology, Shalamar Hospital, Lahore for 6 months. Then the selected females were divided randomly into 2 equal groups. In group A, females had manual vacuum procedure while in group B, females had evacuation & curettage under general anesthesia. After 12 hours of the procedure, ultrasonography was done to confirm complete evacuation. Results: The mean age of the patients was 29.87 ± 6.71 years, the mean gestational age was 8.06 ± 2.82 weeks. The effectiveness was noted in 248 (91.85%) patients. Statistically, manual vacuum showed significantly more effective as compared to evacuation & curettage procedure in the management of incomplete miscarriage i.e. p-value = 0.008. Conclusion: It has been proved that manual vacuum aspiration is more effective than traditional evacuation & curettage in the management of incomplete miscarriage.